Novel Base Station MIMO Antennas with Enhanced Spectral Efficiencies Using Angular Reuse - Miguel Mora-Andreu; David A. Sánchez-Hernández (International Journal of Antennas and Propagation)
The true polarization diversity (TPD) technique is combined with the spatial diversity technique in novel MIMO antenna array geometries with a large number of elements. The use of a large number of elements requires some angular reuse within the array for polarization diversity. With designs compatible with existing base station antenna array configurations, the novel geometries with combining diversity schemes are shown to be able to achieve near the maximum spectral efficiencies. True polarization diversity (TPD) schemes are found to be an excellent complement to more conventional spatial diversity schemes for obtaining optimum MIMO array performance in base station antennas.